Scales of Stress Heterogeneity Near Active Faults in the Santa Barbara Channel, Southern California - Patricia Persaud; Edward H. Pritchard; Joann M. Stock (Geochemistry, Geophysics, Geosystems, 2020)
Abstract The Santa Barbara Channel represents the offshore portion of the Ventura Basin in Southern California. Ongoing transpression related to a regional left step in the San Andreas Fault has led to the formation of E‐W trending en‐echelon fault systems that accommodate localized shortening across the basin. Recent studies have suggested that faults within the channel could be capable of a multisegment rupture and producing a Mw 7.7–8.1 tsunamigenic earthquake. However, dynamic rupture models producing these results do not account for stress heterogeneity. With only sparse information available on the stress field in this region, further borehole‐derived stress constraints are essential for obtaining a more comprehensive understanding of the hazards related to the complex fault systems. We used caliper logs from 19 wells obtained from industry to identify stress‐induced borehole breakouts beneath the Holly and Gail oil platforms in the channel. Our newly developed forward modeling technique provides constraints on the orientations and relative magnitudes of the three principal stresses. At Gail, we determine a reverse faulting stress regime (SHmax = 1.7; Shmin = 1.6; SV = 1.0) and an SHmax azimuth of N45°E. Our results are consistent with local structures, which reflect deeper regional scale trends, and with similar studies onshore nearby. At Holly, an SHmax rotation from ~N36°W to ~N57°E occurs across ~100 m depth in a single well and differs from nearby results, indicating that short‐length scale (<10 km laterally and <1 km in depth) stress heterogeneity is associated with complex changes in fault geometry.